2018
DOI: 10.1016/j.sjbs.2018.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Recent approaches for control of E. coli and respiratory complex in Middle East

Abstract: This study was conducted on 100 one-day-old broiler chicks to evaluate the effect of Poulvac E. coli vaccine in reduction of clinical signs and complications after concurrent infectious bronchitis virus (variant 02) and virulent E. coli O78 challenges. The birds were evaluated for clinical signs, mortality for 7 days post-infection, PM lesion score, average body weight and serological evaluation. Re-isolation and RT-PCR for the challenging infectious bronchitis virus (IBV) variant 02 were conducted thereafter.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 18 publications
2
11
0
Order By: Relevance
“…In addition, they have demonstrated the cross-resistance to other E. coli serotypes, but achieved the greatest protection in the case of homologous infection. Galal et al. (2018) have additionally reported that chickens vaccinated against colibacillosis reached better BW gains after simultaneous experimental infection with infectious bronchitis virus ( IBV ) and E. coli , that their mortality rate was lower, and that the intensity of development of pathological lesions typical of colibacillosis decreased as well.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they have demonstrated the cross-resistance to other E. coli serotypes, but achieved the greatest protection in the case of homologous infection. Galal et al. (2018) have additionally reported that chickens vaccinated against colibacillosis reached better BW gains after simultaneous experimental infection with infectious bronchitis virus ( IBV ) and E. coli , that their mortality rate was lower, and that the intensity of development of pathological lesions typical of colibacillosis decreased as well.…”
Section: Introductionmentioning
confidence: 99%
“…Live vaccines have been repeatedly proven to contribute positively to bird protection [ 26 , 27 , 28 , 29 , 30 ], although exceptions have also been reported [ 31 ]. A commercial live vaccine is presently available in most regions; it was registered in the EU in 2013 [ 32 ] and it is an attenuated O78 E. coli strain and provides effective protection upon challenge with O78 wild strains [ 33 ]. However, this type of vaccine is less efficient against heterologous strains (i.e., belonging to other serogroups) [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that treatments with the Poulvac E. coli vaccine significantly reduced the severity of lesions in both the trachea and liver compared to the non-vaccinated group D1(En-Nv-Ch) with a higher level of protection in group A1 (LS-7dV-Ch) 21 , 25 . The serum biochemical parameters were aligned with clinical signs, mortality, necropsy, and histopathology findings where group A1(LS-7dV-Ch) showed significant differences in total protein, urea, and creatinine compared to group D1 (En-Nv-Ch).…”
Section: Discussionmentioning
confidence: 78%
“…Results have shown that the use of Poulvac E. coli on day-old or day 7 with prior antibiotic prophylaxis in the first three days does not affect the immune response to these vaccines. Also, there was an improvement in both viral agents' immune responses, particularly in group A1 (LS-7dV-Ch) 21 , 24 .…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation